Design of an open-source software system for water temperature monitoring - Joao E M Perea Martins (Computational ecology and software, 2025)
This article presents the software and hardware components of an open-source system designed for water temperature monitoring. The system can handle measurements from up to eight sensors at user-defined time intervals. It was designed with the waterproof temperature sensor model DS18B20, an Arduino board and a computer. The Arduino-based program reads the sensors data and transmits the temperature values to the computer in real-time via a serial communication. The computer software has an intuitive user interface to ensure an easy operation, and it displays the temperatures numerically, generates graphs, and allows the user to save the data to a disk at any time. Besides the Arduino and the sensors, the hardware setup requires only a single additional resistor making assembly straightforward. This article details the Arduino and the computer source code programs, and the satisfactory system results have motivated the work presentation.